Ambient temperature and dengue hospitalization in Brazil A 10-year period case time series analysis - Lopes, Rafael [UNESP]; Basagaña, Xavier; Bastos, Leonardo S.L.; Bozza, Fernando A.; Ranzani, Otavio T. (Wolters Kluwer, 2024)
Background: Dengue has an increased worldwide epidemic potential with the global rising temperature due to climate change. Heat and rainfall are known to influence seasonal patterns of dengue transmission over the course of weeks to months. However, there is a gap in knowledge about the short-term effect of heat on dengue severity. We aimed to quantify the effect of ambient temperature on dengue hospitalization risk in Brazil. Methods: Daily dengue hospitalization counts and average daily ambient temperature from 2010 to 2019 were analyzed from Brazil. We applied the case time series design combined with a distributed lag nonlinear model framework to estimate relative risk (RR) estimates for dose–response and lag–response structures for the association of temperature and dengue hospitalization. We estimate the overall dengue hospitalization RR for the whole country as well as for each of the five macroregions. Results: A total of 579,703 hospital admissions due to dengue occurred between 2010 and 2019. We observed a positive association between high temperatures and a high risk of hospitalization across the country. Under extreme heat (95th percentile of temperature), the RR was 3.47 (95% confidence interval: 2.88, 4.19) compared with minimum hospitalization risk. This association was mainly driven by an immediate effect of heat (lag 0) and was similar for the Northeast, Center-West, Southeast, and South regions, but unclear for the North. The risk was of greater magnitude among females and those aged ≥65 years. Conclusion: Short-term high temperatures are associated with an increase in the risk of hospitalization by dengue.
Keywords: Dengue; Heat; Hospitalization; Temperature